(untitled) (Physical Education, Health and Social Sciences, 2025)
Developing countries have evolved into having rapid urban growth in terms of cities, especially the medium-sized ones, which tend to expand without proper planning regulations. The spatial temporal dynamics and directional patterns of the urban growth have key importance in terms of sustainable land management and urban planning. This paper is an analysis of the spatio-temporal development process and directional growth of Nawabshah City, Sindh, Pakistan, on the basis of multi-temporal Landsat satellite images and Geographic Information System (GIS) methods between the year 1990 and 2024. To extract the built-up and non-built-up land cover classes, ArcMap classification was conducted on Landsat TM and OLI images in 1990, 2001, 2013, 2020 and 2024. Descriptive statistics and ANOVA were regarded to conduct the analysis of urban expansion intensity, spatial growth patterns and the statistical variations. Findings indicate that built-up area has been increasing at a steady accelerating rate of 4.57km2 in 1990 to 11.27km2 in 2024 with the process changing towards dispersed, corridor-driven and peripheral with the growth process. The results point to the impact of the transportation infrastructure, population increase and socio-economic development on the spatial reorganization of the city. The paper highlights how urban monitoring and strategic spatial planning of city in GIS is necessary to control the future development in urban areas in Nawabshah and other secondary cities like Nawabshah in Pakistan.